2018
DOI: 10.1007/s00590-018-2161-7
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative treatment of osteochondral lesions of distal tibial plafond

Abstract: Osteochondral lesions of the distal tibia represent a challenge for the orthopedic surgeon because of their difficulty diagnostic and rarities. The high incidence of good outcome in our series indicates that the one-step BMDCT could be a valid option for the treatment of this rare type of lesions. Further studies with a longer follow-up and more accurate imaging studies are necessary to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(57 citation statements)
references
References 27 publications
0
57
0
Order By: Relevance
“…Ten articles were included in the review (Figure 1, Table 1). 2,3,5,10,13,18,20,24,29,36 All studies were published in 2000 or later and were deemed level 4 evidence, except for Elias et al 15 The mean Methodological Index for Non-randomized Studies score of the 5 surgical treatment studies 3,12,23,27,33 was 8.6 (range, 8-10); each of these was a noncomparative case series.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten articles were included in the review (Figure 1, Table 1). 2,3,5,10,13,18,20,24,29,36 All studies were published in 2000 or later and were deemed level 4 evidence, except for Elias et al 15 The mean Methodological Index for Non-randomized Studies score of the 5 surgical treatment studies 3,12,23,27,33 was 8.6 (range, 8-10); each of these was a noncomparative case series.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Cuttica et al 12 performed lateral ankle ligament stabilization in 3 of 13 patients (2 isolated, 1 coexisting). Furthermore, Baldassarri et al, 3 in evaluating BMDCT for isolated OLTPs, found inversion ankle sprain as a traumatic cause in 20 of 27 patients and noted that those with impingement findings had a worse rate of improvement in AOFAS scores at 12-month follow-up (P ¼ .029). The findings from these studies suggest that additional ankle pathologies such as instability and trauma may affect the incidence, natural history, or outcomes of treatment of OLTPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reports of new attempts are as follows: bone marrow–derived cell transplantation, 8 micronized allograft cartilage matrix transplantation, 9 and bone marrow aspirate concentrate combined with biologic scaffold transplantation 10 . These techniques have satisfactory clinical results but they are still under development because long-term and high-evidence studies are required.…”
Section: Discussionmentioning
confidence: 99%